2007
DOI: 10.1094/cchem-84-5-0527
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Rice Starch Modified by Hydrothermal Treatments

Abstract: Rice starches of long grain and waxy cultivars were annealed (ANN) in excess water at 50°C for 4 hr. They were also modified under heat‐moisture treatment (HMT) conditions at 110°C with various moisture contents (20, 30, and 40%) for 8 hr. The modified products were analyzed by rapid‐viscosity analysis (RVA), differential scanning calorimetry (DSC), and X‐ray diffraction (XRD). Generally, these hydrothermal treatments altered the pasting and gelling properties of rice starch, resulting in lower viscosity peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
50
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 23 publications
10
50
0
1
Order By: Relevance
“…The X-ray diffraction pattern of raw rice showed the A pattern which disappeared in instant rice porridges. Instant rice porridges showed the V-type pattern, or the diffraction peaks at 2θ = 13° and 20°, which indicated that the crystalline structure of the rice starch granules was destroyed during the drying process (Ratnayake and Jackson, 2007).This result agrees well with Miyoshi (2002), Prasert andSuwannaporn (2009), andShih et al, (2007).…”
Section: Resultssupporting
confidence: 75%
“…The X-ray diffraction pattern of raw rice showed the A pattern which disappeared in instant rice porridges. Instant rice porridges showed the V-type pattern, or the diffraction peaks at 2θ = 13° and 20°, which indicated that the crystalline structure of the rice starch granules was destroyed during the drying process (Ratnayake and Jackson, 2007).This result agrees well with Miyoshi (2002), Prasert andSuwannaporn (2009), andShih et al, (2007).…”
Section: Resultssupporting
confidence: 75%
“…Noticeably, higher amount of chlorophyll b was found in the BSC coated milled rice before cooking, as also observed previously for chlorophyll a. This could be also explained by higher V-type crystallinity of the instant rice surface compared to milled rice [24]. In addition, DE of maltodextrin did not affect chlorophyll b of the BSC coated milled rice, while the higher amount was found with higher DE for the coated instant sample, meaning better enhancement of encapsulability.…”
Section: Chlorophyll Contentssupporting
confidence: 83%
“…Crystalline structure which is responsible for water barrier on its surface could be possible explanation of this result. The formation of amylose-lipid complexes (Vtype crystalline structure) occurred during heat-moisture treatment in instant rice process [23,24]. This pattern of crystalline was detected either because more complexes were formed during heating or crystalline regions had increased in size after gelatinization [25].…”
Section: Optimization Of Coating Methodsmentioning
confidence: 99%
“…The effects of HMT on various aspects of rice starch properties have been reported by several researchers (Hormdok & Noomhorm, 2007;Khunae, Tran, & Sirivongpaisal, 2007;Shih, King, Daigle, An, & Ali, 2007;Zavareze, Storck, Suita de Castro, Schirmer, & Dias, 2010), whereas relatively little work has been done on properties of rice flour (Cham & Suwannaporn, 2010;Lorlowhakarn & Naivikul, 2006). None of the reviewed works involved comparison of starch and flour from the same source of rice kernels (the same variety, batch, etc.)…”
mentioning
confidence: 99%